2014
DOI: 10.5152/imj.2013.74429
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variations of the Paranasal Sinus Region: Evaluation with Multidetector CT

Abstract: In this study, we aimed to evaluate the frequency of anatomic variations of the paranasal sinus region by using multidetector computerized tomography (MDCT). Methods: Between November 2009 and February 2012, 5832 adult patients (2980 females, 2852 males) with a mean age of 39.1±15.4 years (range; 19-85), who underwent MDCT imaging of the paranasal sinus region, were retrospectively evaluated by using the picture archiving and communication system (PACS). All the images were evaluated by three radiologists. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…[4,5] The uncinate process pneumatization rate in our research was 5.3 %, the ACP pneumatization rate was 26.7%, and the PP pneumatization rate was 33.3%, all in accordance with what previous studies in the literature have claimed. [1][2][3][4][5][6][7] We classified optic nerve type in the sphenoid sinus according to the classification system proposed by Delano et al [1] Optic nerve Type 1 (54.2%) was the most frequent nerve type, followed by Type 4 (16.9%). In the study by Delano et al, and one by Al-Tameemi et al, the type 1 optic nerve was the most prevalent type, followed by type 2 [1,9] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[4,5] The uncinate process pneumatization rate in our research was 5.3 %, the ACP pneumatization rate was 26.7%, and the PP pneumatization rate was 33.3%, all in accordance with what previous studies in the literature have claimed. [1][2][3][4][5][6][7] We classified optic nerve type in the sphenoid sinus according to the classification system proposed by Delano et al [1] Optic nerve Type 1 (54.2%) was the most frequent nerve type, followed by Type 4 (16.9%). In the study by Delano et al, and one by Al-Tameemi et al, the type 1 optic nerve was the most prevalent type, followed by type 2 [1,9] .…”
Section: Discussionsupporting
confidence: 92%
“…[5] Mladina et al determined the incidence of NSD by anterior rhinoscopy, whereas paranasal sinus CT was used by Turna et al and Onwuchekwa et al [3,4,5] The middle concha pneumatization rate was 44.4%, and the superior concha pneumatization rate 13.3% in this study, where only bulbous type of middle turbinate pneumatization was included. In the study of Turna et al [4] , the concha bullosa rate was 57.2%, and the superior concha pneumatization rate 17.9% . In the study by Onwuchekwa et al, [5] the concha bullosa rate was 32.7%, and the superior concha pneumatization rate was 6.3%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is similar to various literatures in the past. Narendra kumar and Subramaniam Haller cell (HC) 10 15.3% Table- presented it as 76% whereas Turnaet al 10 15 This study showed a prevalence of 58.4%, correlating with the studies of Bolger 16 et al and Khojastepour 17 et al Agger Nasi cells are defined as the anterior-most Anterior Ethmoidal cell, Located anterior to the nasolacrimal duct. The plane of maxillary sinus infundibulum lies posterior to it.…”
Section: Discussionsupporting
confidence: 58%
“…Li et al [33] reported the unilateral and bilateral protrusion as 8.68% and 20.57%, respectively. In the study of Turna et al [34], protrusion and dehiscence of ICA were observed in 3% and 24 0.5% of the subjects, respectively. Parvathy et al [35] reported that protrusion of ICA was found in 23.3% of cases (19M; 16F), of whom 42.9% were bilateral, 34.3% were right sided and 22.9% were left sided.…”
Section: Oc Prevalencementioning
confidence: 87%